How China's WTO accession affects rural economy in the less-developed regions: a multi-region, general equilibrium analysis - Diao, Xinshen; Fan, Shenggen; Zhang, Xiaobo (International Food Policy Research Institute, 2002)
This study constructs a regional CGE model of China to analyze the differential regional impacts of China’s WTO accession on agricultural production, trade, and farmers’ income. The results show that China’s WTO accession will generally improve the total welfare but will widen existing gaps among regions and sectors. It is expected that the agricultural sector will suffer if only agricultural trade is liberalized, as cheap imports of agricultural products, particularly grains, will increase and domestic agricultural production and farmers’ agricultural income will decline. Full trade liberalization, i.e., lifting trade barriers in both agriculture and non-agriculture will benefit farmers and agriculture at the national level. However, the increase in rural income is still smaller than the increase in urban income, which implies that the rural- urban income gap may be further widened. Furthermore, among the regions, the less-developed rural areas will benefit little or even suffer because their major production activities and income sources are still from agriculture, especially from traditional agricultural activities such as grain production.